Human-wildlife interactions: An ecological perspective (Zoological Records and Reviews, 2024)
Human-wildlife interactions (HWI) span a continuum from mutualistic to highly antagonistic, shaping both wildlifepopulation dynamics and human livelihoods across urban, agricultural, and wilderness landscapes. This studycharacterises the ecological structure and consequences of HWI across four interaction categories -- wildlife crop-raiding,large carnivore livestock depredation, wildlife-borne zoonotic disease transmission, and urban wildlife habituation -- usingfield data from 24 study sites in Finland, Italy, and France spanning 2020-2023 (n = 6,847 interaction events, 18 focalwildlife species). Generalised linear mixed models revealed that crop-raiding frequency by wild boar (Sus scrofa)increased with forest-crop edge density (beta = 0.48 +- 0.09, z = 5.33, p < 0.001) and was negatively related to huntingpressure index (beta = -0.31 +- 0.08, z = -3.88, p < 0.001). Carnivore livestock depredation events (wolf Canis lupus, lynxLynx lynx) were best predicted by livestock enclosure quality score (beta = -0.62 +- 0.11) and wild prey biomass index(beta = -0.44 +- 0.10), with depredation rates 4.8-fold higher at farms with inadequate enclosures relative to those withpredator-proof infrastructure. Zoonotic pathogen prevalence (Echinococcus multilocularis, Borrelia burgdorferi) in wildlifereservoir hosts was positively correlated with human population density at peri-urban sites (r = 0.71, p < 0.001). Urbanwildlife habituation indices for red fox and raccoon dog were 2.4-fold higher at sites with supplementary feeding byresidents compared to non-feeding sites. These findings provide an evidence-based framework for HWI managementprioritisation under the EU Biodiversity Strategy 2030 and national coexistence policy frameworks.
Keywords: EU Biodiversity Strategy; coexistence; habituation; Canis lupus; Sus scrofa; urban wildlife; zoonotic disease; livestock depredation; crop-raiding; human-wildlife interaction